RISIKO KENAIKAN HEMATOKRIT TERHADAP TERJADINYA RENJATAN PADA KASUS DEMAM BERDARAH DENGUE - Sumakto, Sumakto; Santoso, Nurtjahjo Budi; Nugroho, Susanto; Kawurjan, Siti Lintang (Fakultas Kedokteran Universitas Brawijaya, 2004)
ABSTRACT Shock is life threatening feature of DHF it must be manage properly through close clinical and laboratory observations. This was a pre-eliminary study to evaluate hematocrit (Hct) increased where shock occurs on dengue hemorrhagic fever (DHF) or dengue shock syndrome (DSS). The WHO criteria was used to diagnose DHF, with two or more clinical criteria with trombocytopenia (≤ 100.000) and Hct increase ≥ 20 %. Examination of hemoglobin (Hb), Hct, thrombocytes and leucocytes were done in RSU Dr. Saiful Anwar Central Laboratory everyday during hospitalized. The increase of Hct percentage and Hct/Hb ratio calculation were based on the result of lowest dan highest Hct and Hb examination. The data obtains was analysed with t-test using SPSS version 10.0 programme. From 30 DHF cases, 23 (76.66%) non DSS and 7 (23.77%) DSS. The average Hct increase in all patients from serial examinations was 21.09% (SD= 2.32%). However, in 7 DSS patients the average Hct increase was 23.79% (SD= 3.84%) higher than the 23 non DSS patients (20.28%; SD= 0.25%). It was observed that the Hct increase in DSS patients was higher than that for non DSS patients. This high Hct level of 23.79% increases the likelihood of shock by 2.5 times compare with an Hct rise of 20.28%. There was a significant difference in the highest and lowest Hct/Hb ratio between DSS and non DSS cases (p= 0.000). Keywords : dengue hemorrhagic fever, dengue shock syndrome, hematocrit increase, Hct/Hb ratio